Practice, governance, and culture characteristics of lived experience organisations, and evidence of efficacy: A scoping review protocol. - Jessica E Opie; An Vuong; Alexandra Macafee; Hanan Khalil; Natalie Pearce; Erandathie Jayakody; Christropher Maylea; Jennifer E McIntosh (PLoS ONE)
Background Mental health policy and service design is increasingly recognizing the importance of the lived experience voice and its inclusion in all aspects of work. Effective inclusion requires a deeper understanding of how best to support lived experience workforce and community members to meaningfully participate in the system. Objectives This scoping review aims to identify key features of organizational practice and governance that facilitate the safe inclusion of lived experience in decision-making and practice within mental health sector contexts. Specifically, the review focuses on mental health organizations devoted to lived experience advocacy or peer support or those in which lived experience membership (paid or voluntary) is central to advocacy and peer support operations. Methods This review protocol was prepared with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols and registered with the Open Science Framework. The review will be guided by the Joanna Briggs Institute methodology framework and is being conducted by a multidisciplinary team including lived experience research fellows. It will include published and grey literature, including government reports, organizational online documents, and theses. Included studies will be identified through comprehensive searches of five databases: PsycINFO (Ovid), CINAHL (EBSCO), EMBASE (Ovid), MEDLINE (Ovid), and ProQuest Central. Studies published in English from 2000 onwards will be included. Data extraction will be guided by pre-determined extraction instruments. Results will be presented in a Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews flow chart. Results will be presented in tabular form and narratively synthesized. The planned commencement and completion dates for this review were July 1, 2022 and April 1, 2023. Discussion It is anticipated that this scoping review will map the current evidence base underpinning organizational practices in which lived experience workers are involved, specifically in the mental health system. It will also inform future mental health policy and research. Trial registration Registration: Open Science Framework (registered: July 26, 2022; registration DOI: 10.17605/OSF.IO/NB3S5).